1995
DOI: 10.1002/dev.420280406
|View full text |Cite
|
Sign up to set email alerts
|

Development of water‐immersion produced analgesia

Abstract: Nociceptive and antinociceptive systems change dramatically during the first 10 days of life in rats. The present studies sought to determine whether exposure to water stress can produce analgesia during this period, and when in the ontogeny changes in magnitude and duration of such stress-induced analgesia occur. It was found that exposure to water reliably induced analgesia as early as 3 days postnatally. This analgesia increased in magnitude and duration at the age of 17-20 days, when supra-spinal descendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Regarding age, however, there is no clear pattern of increased or decreased sensitivity to SIA as the subject grows older. One study has shown that the development of analgesia induced by water immersion occurs in rats as young as 3 days old with a significant increase in analgesia by 17 days (Stolberg and Frenk, 1995). These workers propose that the increase in analgesia at this age is due to the development of supraspinal descending pain inhibition.…”
Section: The Effects Of Age and Experience On Siamentioning
confidence: 99%
“…Regarding age, however, there is no clear pattern of increased or decreased sensitivity to SIA as the subject grows older. One study has shown that the development of analgesia induced by water immersion occurs in rats as young as 3 days old with a significant increase in analgesia by 17 days (Stolberg and Frenk, 1995). These workers propose that the increase in analgesia at this age is due to the development of supraspinal descending pain inhibition.…”
Section: The Effects Of Age and Experience On Siamentioning
confidence: 99%
“…Skin sensory nerve endings are stimulated. Both animal and human studies suggest that sensory overflow may be the mechanism by which pain is less well perceived when the affected body part is immersed in water [187,188]. Pain modulation is consequently affected with a rise in pain threshold, which increases with temperature and water turbulence, producing the proposed therapeutic effect of agitated whirlpool immersion [189,190].…”
Section: Applications In Pain and Psychiatric Rehabilitationmentioning
confidence: 99%
“…Aquatic environment showed many beneficial effects on pain perception. Skin sensory nerve endings are stimulated, and different studies suggest that sensory overflow may act as pain modulator, increasing the pain threshold, improving pain and function (22). The hydrostatic effects of immersion significantly reduce soft tissue edema (23).…”
Section: Discussionmentioning
confidence: 99%
“…3 subjects were excluded because associated injuries were detected during surgery. Twenty-four patients met the inclusion criteria, 12 for group (13 males, 11 females; mean age 28 for group A, 26.3 for group B; range[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. No statistically significant differences were observed for variables such as age, sex, height, weight, BMI.…”
mentioning
confidence: 99%